Determinants of The Indonesian Mining Sector’s Audit Delay - Dinda Puteri Denise Quinones; Alfonsa Dian Sumarna (IJHCM (International Journal of Human Capital Management), 2023)
This main research focus is to examine the factors that influence audit delay with a new period of the year and mining sector sample. Audit delay is a very important problem to pay attention to in company financial reporting. Various previous studies still have inconsistent results. This study examines the effect of Profitability, KAP Reputation, Size of the Audit Committee, and the COVID-19 Pandemic on Audit Delay in mining sector companies for the 2018-2021 period. The sampling method used was purposive sampling. The samples in this study were 17 mining sector companies listed on the Indonesia Stock Exchange, so the research panel data totaled 68. This study uses descriptive statistical analysis techniques, model tests, classical assumption tests, regression analysis, and hypothesis testing with the EViews 12.0 program. The results of the study show that the profitability and reputation of KAP do not have a significant effect on audit delay, the size of the audit committee and the COVID-19 pandemic have a significant effect on audit delay.